Strongly symmetric spectral convex bodies are Jordan algebra state spaces - Hilgert, Joachim; Barnum, H.

Lizhen Ji und Athanase Papadopoulos (Hrsg.): Sophus Lie and Felix Klein: The Erlangen Program and Its Impact in Mathematics and Physics. European Mathematical Society 2015 - Hilgert, Joachim (Mathematische Semesterberichte)

Brian W. Kernighan: Millions billions zillions – defending yourself in a world of too many numbers. Princeton University Press 2018 - Hilgert, Joachim (Mathematische Semesterberichte)

Joseph Honerkamp: Denken in Strukturen und seine Geschichte – Von der Kraft des mathematischen Beweises (Springer 2018) - Hilgert, Joachim (Mathematische Semesterberichte)

Øystein Linnebo: Philosophy of Mathematics (Princeton University Press 2017) - Hilgert, Joachim (Mathematische Semesterberichte)

Jost-Hinrich Eschenburg: Sternstunden der Mathematik. Springer 2017 - Hilgert, Joachim (Mathematische Semesterberichte)

Heilung durch Kunst? Schlingensiefs Reenactments der Avantgarden der Performancekunst (Ball, Brus, Beuys und Nitsch) - Hilgert, Joachim (Schlingensief und die Avantgarden)

Hoch inferentes Rating: Kognitive Aktivierung während der Kunstrezeption - Schmidt, Rebekka (Technischer Bericht zu den PERLE-Videostudien. Band 2: Beobachtungssysteme zur Beschreibung und Qualität von Grundschulunterricht)

Den Kunstunterricht aktiv beforschen – forschendes Lernen im Praxissemester - Schmidt, Rebekka (Der professionalisierte Blick: Forschendes Studieren in der Kunstpädagogik)

Zur Berufsorientierung südeuropäischer DaF-Hochschullehrpläne - Prikoszovits, Matthias (Sprache im Beruf)
Keywords: General Medicine

«HoPE iS BACK» – Poetisches auf urbanen Wandflächen - Tophinke, Doris (Leseforum.ch – Online-Plattform für Literalität)

"Hömma". Emblematischer Gebrauch von Dialektausdrücken - Tophinke, Doris; Ziegler, Evelyn (Praxis Deutsch)

Dialekte heute

Einleitung (des Themenheftes): Die Stadt als öffentlicher Kommunikationsraum - Tophinke, Doris; Ziegler, Evelyn (Zeitschrift für Germanistische Linguistik)

Mobile Foto-Filter – Von technischer Entstörung und bildästhetischer Aufwertung - Schulz, Christian (Medienobservationen)

Digitalisierung in den Sparkassen Ost-und West-Berlins - Schmitt, Martin (Wendezeiten. Sparkassen in historischen Umbrüchen am Beispiel Berlins)
Keywords: Wiedervereinigung; Wende; Sparkasse; Berlin; Stuttgart; West-Berlin; Deutschland {<}DDR{>}; Deutschland {<}Bundesrepublik{>}

Socialist Life of a U.S. Army Computer in the GDR’s Financial Sector: Import of Western Information Technology into Eastern Europe in the Early 1960s - Schmitt, Martin (Histories of Computing in Eastern Europe)

Histories of Computing in Eastern Europe - Leslie, Christopher; Schmitt, Martin

Kulturtransferforschung und Musikwissenschaft - Münzmay, Andreas (Zwischen Transfer und Transformation: Horizonte der Rezeption von Musik)
Discusses the research paradigm of ‘transferts culturels’ (cultural transfers), as established by French C.N.R.S. scholars Michel Espagne and Michael Werner in the 1980s and rapidly evolving in the context of French-German research after 1989, from the point of view of musicology. Ideological categories like ‘nation’ and ‘culture’ are weighed against frames that allow for more precise definitions, like local/regional repertoires or culture politics. Likewise, the opposed theoretical concepts of ‘reception’ and ‘production’ fundamentally affect the conceptualization of the musical ‘work’ entity. Taking cultural transfers into account has helped stimulating practice-oriented views of music history that no longer consider modifications or adaptations of works only as derivatives or even misunderstandings of ‘the original’, but, to the contrary, acknowledge them as historical facts and cultural expressions in their own rights. The examples of Richard Wagner’s Die Meistersinger von Nürnberg and Eduard Hanslick’s Die moderne Oper show how this was already a controversial issue in the 19th century under the impression of the international nature of the standard (French) opera repertoire of the time. A concluding section points out the possibilities for the coverage of culture transfer processes arising from the implementation of the FRBR (Functional Requirements for Bibliographic Records) model in bibliographic authority data on the ‘work’ level. (Autor)

Digitalisierung im organisierten Sport – Eine Analyse zur Nutzung digitaler Instrumente in Sportvereinen - Riedl, Lars; Ehnold, Peter; Schlesinger, Torsten (Sciamus - Sport und Management, 4)
Trotz hoher Aktualität und steigender Bedeutung liegen zum Thema Digitalisierung im Sportverein bisher kaum empirische Erkenntnisse vor. Der vorliegende Beitrag setzt sich mit folgenden Fragestellungen auseinander: (i) In welchem Umfang und zu welchem Zweck nutzen Sportvereine digitale Instrumente? (ii) Welche vereinsspezifischen Faktoren determinieren das jeweilige Nutzungsverhalten? Hierzu wurde eine Stichprobe von n=787 Sportvereinen aus Österreich und Deutschland generiert. Es zeigt sich, dass digitale Instrumente vor allem zur internen und externen Kommunikation sowie zur Bewältigung klassischer Verwaltungsaufgaben eingesetzt werden. Das Ausmaß der Nutzung hängt einerseits von vereinsexternen Bedingungen ab. So zeigt sich dahingehend ein Ländereffekt, dass in Deutschland digitale Instrumente stärker genutzt werden als in Österreich. Darüber hinaus haben Auflagen seitens der Verbände zur Verwendung bestimmter Software (z.B. für die Meldung von Wettkampfergebnissen) einen wichtigen Einfluss. Andererseits bestimmen vereinsinterne Faktoren wesentlich das Nutzungsverhalten. Positiv wirken vor allem die Vereinsziele ‚Engagement/Erfolg im Leistungssport‘ und ‚Wollen Vorreiterrolle bei der Digitalisierung einnehmen‘. Negativ wirken eine fehlende Strategie im Umgang mit digitalen Instrumenten sowie die Einschätzung, dass digitale Prozesse nicht zur eigenen Vereinskultur passen.

Die Funktion des Sports im Gesundheitsmanagement der öffentlichen Verwaltung - Sennefelder, Lisa

Zwischen Komposition, Aufführung und Herausgabe - Ried, Dennis (Mitteilungen der IMRG)

Creating, transforming and representing data at Baumann-Digital and Joachim-Raff-Archiv - Ried, Dennis

Creating, transforming and representing data at Baumann-Digital and Joachim-Raff-Archiv - Ried, Dennis

»Ein gar kräftigliches, nie versiegendes Heilmittel« – Max Regers Klavierbearbeitungen Bach’scher Orgelwerke - Ried, Dennis; Grafschmidt, Christopher

Vokalwerke mit Orgelbegleitung und weiteren Instrumenten

Prospektives versus retrospektives Argumentieren. Redebeiträge vor und nach einer parlamentarischen Abstimmung - Kunert, Irene Dorothea (Linguistik Online)
This study aims to investigate the linguistic differences between an argumentation referring to a potential future action (prospective argumentation) and one justifying a past action (retrospective argumentation) in the parliamentary arena. It is based on the analysis of German and French speeches taken from the protocols of the plenary sessions of the European Parliament.
In a plenary session, parliamentary votes are preceded by a general debate. During this debate, speakers may give reasons supporting their own choice in an upcoming vote, but they may also try to persuade other Members of Parliament to vote the same way. This argumentation is prospective. After the vote, Members may give an oral or written explanation of vote designed to justify their decision. The argumentative orientation in this case is retrospective. In an exemplary approach, 50 speeches per language (German/French) and communication situation (prospective/retrospective) will be analyzed. The study argues that the macrostructure of the speeches is influenced by the orientation of the conclusion: In a prospective argumentation, speakers tend to first present their arguments before coming up with their conclusion, the conclusion being a declaration of one’s own intent to vote or a recommendation for other Members of Parliament. In a prototypical explanation of vote, the conclusion precedes the arguments. Special attention is given to the analysis of argument and conclusion markers. The study tries to show that conclusion markers are relatively more frequent in prospective argumentation, while retrospective argumentation makes broader use of argument markers.

Saussure – encore et toujours - Albrecht, Jörn; Kunert, Irene Dorothea (Historiographia Linguistica)

Der Argumentationsindikator prouver und seine deutschen Äquivalente. Eine Studie zum Gebrauch metaargumentativer Verben im deutsch-französischen Sprachvergleich - Kunert, Irene Dorothea (Comparatio delectat III. Akten der VIII. Internationalen Arbeitstagung zum romanisch-deutschen und innerromanischen Sprachvergleich, Innsbruck, 29.8.-1.9.2016)

Why teachers cooperate: an expectancy-value model of teacher cooperation - Drossel, Kerstin; Eickelmann, Birgit; van Ophuysen, Stefanie; Bos, Wilfried (European Journal of Psychology of Education)

Musikwissenschaft und Digital Humanities - Stadler, Peter (Historische Musikwissenschaft. Gegenstand – Geschichte – Methodik)

Hard X-ray spectroscopy: an exhaustive toolbox for mechanistic studies (?) - Schoch, Anke; Burkhardt, Lukas; Schoch, Roland; Stührenberg, Kai; Bauer, Matthias (Faraday Discussions)
The hard X-ray spectroscopy methods XAS, valence-to-core XES and higher solution XANES offer unique insights into organometallic reaction mechanisms.

Flexibility Options for Absorption and Distillation to Adapt to Raw Material Supply and Product Demand Uncertainties: A Review - Riese, Julia; Lier, Stefan; Paul, Sarah; Grünewald, Marcus (ChemEngineering)
The chemical industry has to deal with increasing uncertainties regarding the boundary conditions of their production processes. On the one hand, uncertainties affect the availability, quality, and prizes of raw material and energy. On the other hand, the demand side is affected by increasing volatilities in product demand and increasing requirements for product variety. These changing boundary conditions lead to higher needs for flexibility in production processes of the chemical industry. Within this article technical solutions for an enhancement of different forms of flexibility are presented for production concepts and apparatus concepts, respectively. The latter focuses on unit operations for the separation of gas–liquid mixtures. This includes a review regarding transformable, modular production processes and a classification of their field of application. Additionally, concepts for named unit operations on different scales are presented and discussed. The presented concepts are also classified with respect to the different types of flexibility.
Keywords: General Energy; General Engineering; General Chemical Engineering

Modeling and Validating Fixed‐Bed Reactors: A State‐of‐the‐Art Review - Stegehake, Carolin; Riese, Julia; Grünewald, Marcus (ChemBioEng Reviews)
Abstract Modeling of heat and mass transfer in fixed‐bed reactors for heterogeneously catalyzed gas phase reactions is possible using different methods. Homogeneous and heterogeneous continuum models as well as particle resolved modeling of fixed‐bed reactors show high potential for application. Considering those approaches, advantages and disadvantages as well as underlying assumptions and boundary conditions are discussed. Additionally, methods for experimental validation are presented and discussed focusing on the two‐dimensional homogeneous models.
Keywords: Industrial and Manufacturing Engineering; Filtration and Separation; Process Chemistry and Technology; Biochemistry; Chemical Engineering (miscellaneous); Bioengineering

Besetzte Heimat. Eine Spurensuche in Vaterunser-Parodien - Breckner, Anne (Heimatgedanken. Theologische und kulturwissenschaftliche Beiträge)

Rezension zu „Hometown Religion. Regimes of Coexistence in Early Modern Westphalia“ (2016) von Luebke, David M. - Breckner, Anne (Jahrbuch für Westfälische Kirchengeschichte (JWKG))

Bericht: Schulkooperation zwischen Institut für Evangelische Theologie und inklusiver Grundschule – Freudiger Blick in die Zukunft des forschenden Lernens - Breckner, Anne

Bericht: Wie schmeckt der Glaube? Eine Frage – viele Antworten bei außergewöhnlichem, interreligiösem Blockseminar - Breckner, Anne

Multithreaded Software/Hardware Programming with ReconOS/freeRTOS on a Reconfigurable System-on-Chip - Mehta, Jinay D

Religion zwischen Ohnmacht, Bemächtigung und Ermächtigung: Zusammenfassende Perspektiven - Tatari, Muna; Ströbele, Christian; Specker, Tobias (Welche Macht hat Religion? Anfragen an Christentum und Islam)

Numerical Investigation of the Temperature Distribution in PCM-integrated Solar Modules - Grabo, Matti; Weber, Daniel; Paul, Andreas; Klaus, Tobias; Bermpohl, Wolfgang; Krauter, Stefan; Kenig, Eugeny (Chemical Engineering Transactions)

Modellierung und Optimierung von makroverkapselten Latentwärmespeicherelementen - Grabo, Matti; Staggenborg, Christoph; Kenig, Eugeny

GDSU – Qualitätsrahmen Lehrerbildung Sachunterricht und seine Didaktik im Kontext der universitären Ausbildungsphase - Becher, Andrea; Blaseio, Beate; Dunker, Nina; Gläser, Eva; Otten, Michael; Pech, Detlef; Peschel, Markus; Schomaker, Claudia; Tänzer, Sandra

Interactionism in the age of ubiquitous telecommunication - Klowait, Nils (Information, Communication & Society)
Keywords: Library and Information Sciences; Communication

Das Zürcher Ressourcen Modell (ZRM) als Ansatz zur Stressreduktion im Heilungsverlauf - Schneider, Tamara

A convergent evolving finite element algorithm for mean curvature flow of closed surfaces - Kovács, Balázs; Li, Buyang; Lubich, Christian (Numerische Mathematik)
Keywords: Applied Mathematics; Computational Mathematics

Beruf(en) im Verkauf. Gesellschaftliche Bedeutung subjektiver Arbeitsaneignungen. - Krause, Ina; Kupfer, Antonia; Eckert, Falk (Österreichische Zeitschrift für Soziologie)

Ergodic Rate for Fading Interference Channels with Proper and Improper Gaussian Signaling - Soleymani, Mohammad; Santamaria, Ignacio; Lameiro, Christian; Schreier, Peter J. (Entropy)
This paper studies the performance of improper Gaussian signaling (IGS) over a 2-user Rayleigh single-input single-output (SISO) interference channel, treating interference as noise. We assume that the receivers have perfect channel state information (CSI), while the transmitters have access to only statistical CSI. Under these assumptions, we consider a signaling scheme, which we refer to as proper/improper Gaussian signaling or PGS/IGS, where at most one user may employ IGS. For the Rayleigh fading channel model, we characterize the statistical distribution of the signal-to-interference-plus-noise ratio at each receiver and derive closed-form expressions for the ergodic rates. By adapting the powers, we characterize the Pareto boundary of the ergodic rate region for the 2-user fading IC. The ergodic transmission rates can be attained using fixed-rate codebooks and no optimization is involved. Our results show that, in the moderate and strong interference regimes, the proposed PGS/IGS scheme improves the performance with respect to the PGS scheme. Additionally, we numerically compute the ergodic rate region of the full IGS scheme when both users can employ IGS and their transmission parameters are optimized by an exhaustive search. Our results suggest that most of the Pareto optimal points for the 2-user fading IC channel are attained when either both users transmit PGS or when one transmits PGS and the other transmits maximally improper Gaussian signals and time sharing is allowed.
Keywords: General Physics and Astronomy

Robust Improper Signaling for Two-User SISO Interference Channels - Soleymani, Mohammad; Lameiro, Christian; Santamaria, Ignacio; Schreier, Peter J. (IEEE Transactions on Communications)
Keywords: Electrical and Electronic Engineering

Energy-efficient Design for Underlay Cognitive Radio Using Improper Signaling - Soleymani, Mohammad; Lameiro, Christian; Schreier, Peter J.; Santamaria, Ignacio (ICASSP 2019 - 2019 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))